Use of various additives in the production of plum jam - Unuk, Tatjana; Fartek, Doroteja; Grobelnik Mlakar, Silva (Anali PAZU, 2022)
At the Faculty of Agriculture and Life Sciences we determined how various additives in the plum jam affected the sensory assessment of jam. As a basic material we used the 'Čačanska lepotica' plum variety. We added minced cloves, minced ginger and minced orange peel (6 g/L). The additives were chosen upon their aromatic and proven anti-oxidative properties. At the beginning of June 2017, a sensory evaluation was carried out, using a hedonic scale. Panellists assessed the acceptability of smell, colour, taste, consistency, sugar/acid ratio and the overall impression of individual samples of plum jam. At the same time, they also tried to identify the additives. The results of the sensory evaluation show that additives significantly influence the assessment of colour, taste, sugar/acid ratio and an estimate of the overall impression. The highest overall rating received the jam with an addition of orange peel, and the lowest jam with added cloves in concertation 6 g/L of mass. The hypothesis that panellists will reward a familiar taste was refuted.
Keywords: plum jam; cloves; ginger; orange peel; sensory evaluation